PENGAKUAN DAN PERLINDUNGAN HUKUM TERHADAP KEBERADAAN MASYARAKAT HUKUM ADAT BATAK TOBA - Roki Suriadi Pasaribu; Janpatar Simamora (Magister Hukum Universitas HKBP Nommensen, 2022)
The existence of tribute people in the Constitution of 1945, the result of amandement has acknowledged and appreciated in chapter 18 B verses 2. This chapters give position of constitusion to tribute people dealing with state, how they are performed. This coming of tribute people is fact that history can be avoided by government. The regional government is given the authorization to make rules clearly. It can raise conflict either for between regional or regional government with certain law society. Since reformation, law of civil society in indonesia demands much their rights which are stolen by government or other certain groups.